Immunoregulatory effects of morphine on human lymphocytes. - Nair, M P (1997)
It is now well established that parenteral drug abuse is a significant risk factor for contracting human immunodeficiency virus type 1 (HIV-1) infection and subsequently developing AIDS. Earlier studies have shown that morphine can modulate various immune responses and therefore support the premise that morphine is a cofactor in susceptibility to and progression of HIV infection. Dysregulation of interferon (IFN) production, nonspecific apoptosis of T cells, and the immune response to soluble HIV gene products have been associated with potential mechanisms of pathogenesis in HIV disease. The present study was undertaken to examine the immunomodulatory role of morphine on HIV protein-induced lymphocyte proliferative responses, Sendai and Newcastle disease virus-induced alpha IFN (IFN-alpha) and IFN-beta production by lymphocytes and fibroblast cells, respectively, and induction of apoptosis of normal lymphocytes in vitro. Our results demonstrate that HIV protein-induced human lymphocyte proliferative responses were significantly inhibited by morphine in a dose-dependent manner. Furthermore, morphine significantly inhibited both IFN-alpha and IFN-beta production by normal lymphocytes and fibroblasts but induced apoptosis of normal lymphocytes. Inhibition of IFN-alpha production by morphine could be reversed by the opiate receptor antagonist naloxone. This suggests that the immunomodulatory effects of morphine are mediated through the opioid receptor. These studies support a role of morphine as a cofactor in the pathogenesis of HIV infection and describe some of the possible pathologic mechanisms which underlie the immunoregulatory effects of morphine.